Temporal trends in semen concentration and count among 327 373 Chinese healthy men from 1981 to 2019: a systematic review. Issue 7 (27th May 2021) - Lv, Mo-Qi; Ge, Pan; Zhang, Jian; Yang, Yan-Qi; Zhou, Liang; Zhou, Dang-Xia
Abstract: STUDY QUESTION: Are there temporal trends of sperm concentration (SC) and total sperm count (TSC) in Chinese healthy males from 1981 to 2019? SUMMARY ANSWER: Our result indicated a temporal decrease in SC and TSC among 327 373 healthy Chinese men in the recent four decades. WHAT IS KNOWN ALREADY: A review of 61 papers reported a temporal decline in SC and TSC from 1938 to 1990. This trend was later confirmed by a systematic review of 185 published papers from 1981 to 2013. However, the majority of the included individuals were from western countries. In China, whether SC and TSC have declined remains controversial. STUDY DESIGN, SIZE, DURATION: This systematic review of published articles used data extracted from Pubmed, Science Direct, Embase, China-National-Knowledge-Infrastructure (CNKI) and Wanfang Data to assess changes in SC and TSC in China from 1981 to 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 111 studies including 327 373 individuals who provided semen samples from 1981 to 2019 were extracted for the present analysis. Study selection and data extraction were performed by two independent researchers. The trends in SC and TSC were analysed using liner-regression and meta-regression before and after adjusting for potential covariates. Moreover, subgroups, categorised based on geographic region, fertility status or recruitment source, were also analysed. MAIN RESULTS AND THE ROLE OF CHANCE: SC declined significantly (slope liner-regression = −0.748 million/ml/year; P  =   0.005; slope meta-regression = −0.824 million/ml/year; P  <   0.001) between 1981 and 2019 in China. Trends for TSC was similar to that for SC (slope liner-regression = −2.073 million/year; P  =   0.032; slope meta-regression = −2.188 million/year; P  =   0.003). In subgroup meta-regression analyses, males with definite fertility had continuous declines in SC (slope northern group=−2.268, P  =   0.009; slope southern group=−1.014, P  =   0.009) and TSC (slope northern group=−9.675, P  =   0.010; slope southern group=−3.215, P  =   0.042). However, in the unselected group, where fertility status was unknown, the obvious downward trend in SC was only seen in males from Northern regions (slope = −0.836, P  =   0.003). Another subgroup analysis demonstrated that obvious decreases in SC (slope = −1.432, P  <   0.001) and TSC (slope=−4.315, P  =   0.001) were only seen in volunteer groups but not in pre-pregnancy examination groups and other recruitment groups. The results changed minimally in multiple sensitivity analyses. LIMITATIONS, REASONS FOR CAUTION: The validity of the meta-analysis results was limited mainly by the quality of the included studies. Additionally, our study spanned many decades and the recommended criteria for some semen parameter assessments have significantly changed, which may bring about some unavoidable bias. Moreover, the data remain insufficient especially in some provinces of China. WIDER IMPLICATIONS OF THE FINDINGS: The present study is the first study to report significant decreases in SC and TSC in 327 373 healthy Chinese men between 1981 and 2019, indicating a serious reproductive health warning. Further studies on the causes of the declines are urgently needed. STUDY FUNDING/COMPETING INTEREST(S): D.Z. is supported by the National Natural Science Funding of China, Natural Science Funding of Shaanxi Province, Science Funding of Health Department, Shaanxi Province, Fundamental Research Funds for the Central University and the Project of Independent Innovative Experiment for Postgraduates in Medicine in Xi'an Jiaotong University. The authors have no conflicts of interests to declare. TRIAL REGISTRATION NUMBER: N/A